2018
DOI: 10.1039/c8sm01355a
|View full text |Cite
|
Sign up to set email alerts
|

Overcurvature induced multistability of linked conical frusta: how a ‘bendy straw’ holds its shape

Abstract: We study the origins of multiple mechanically stable states exhibited by an elastic shell comprising multiple conical frusta, a geometry common to reconfigurable corrugated structures such as 'bendy straws'. This multistability is characterized by mechanical stability of axially extended and collapsed states, as well as a partially inverted 'bent' state that exhibits stability in any azimuthal direction. To understand the origin of this behavior, we study how geometry and internal stress affect the stability o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The design has the ability to store potential energy in the bending of the folds and the stretching of the faces, similarly to the multistable "bendy straw" design [27]. Interestingly, by changing the size of the design and geometric parameters such as β and ∆z, the amount of structural deformation required for the design to bend and compress can be manipulated, thus allowing us to control the stiffness of the design purely through its geometry.…”
Section: A Parameterized Programmable Crease Patternmentioning
confidence: 99%
“…The design has the ability to store potential energy in the bending of the folds and the stretching of the faces, similarly to the multistable "bendy straw" design [27]. Interestingly, by changing the size of the design and geometric parameters such as β and ∆z, the amount of structural deformation required for the design to bend and compress can be manipulated, thus allowing us to control the stiffness of the design purely through its geometry.…”
Section: A Parameterized Programmable Crease Patternmentioning
confidence: 99%
“…The original bendy straw cell has been described as a pair of conical frusta [12]. Bendy straws can be described in terms of the following parameters: R, the external radius of the cell, the ratio r = r R between the internal and external radii, and a 1 and a 2 , the angles of the top and bottom conical frusta.…”
Section: Geometry and Parametrizationmentioning
confidence: 99%
“…It is worth noting that bistability and even multistability can also be observed in soft structures such as the common bendy straw, which can be either bistable or multistable as required [12]. This was the starting point of our study on the design and construction of a multistable origami tube.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1(a), the unit cell structure of such a flexible straw is a pair of intersecting conical frustra (the outer frustum, Q-T-P and the inner one, Q-P, intersecting at the folds P and Q). By designing the geometrical parameters of the unit cell, a recent study [45] has demonstrated that both the axially folded state and the extended state can be mechanically stable (Figs. 1(b) and 1(c)) for elastic shells.…”
Section: Unit Cell Designmentioning
confidence: 99%